French life insurance lexicography in Canada - AULITTO, Sabrina (JOURNAL OF ADVANCES IN LINGUISTICS, 2016)
In Canada, insurance terminology has long been living a linguistic emergency situation. This paper proposes the study of three different lexicographical works written by French authors of Canadian origin, aimed at normalizing the use of this lexicon. This need started at the end of 19th century, as testified by the Dictionnaire franais-anglais et anglais-français sur la vie written by Naraire Payette. This tradition had its great development in the 1960s, when translators and terminologists launched the refrancization project of the insurance sector, promoted by the Office de la langue franaise.